EXAMINING SOCIAL JUSTICE AND RESERVATION POLITICS IN TUMKUR DISTRICT, KARNATAKA: INSIGHTS AND CHALLENGES - H, Rangaswamaiah; K.C, Suresha (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study examines the impact of social justice and reservation politics in Tumkur district, Karnataka, using data collected from 65 samples. The research explores educational attainment, employment status, political participation, awareness and perceived effectiveness of reservation policies, challenges in accessing education, quality of education, representation in local governance, participation in skill development programs, and satisfaction with government support schemes. The findings indicate that significant challenges persist while reservation policies have facilitated educational and employment opportunities for marginalized communities. The data reveals that a considerable portion of the SC/ST/OBC population has attained secondary education (23.1%) and above, yet financial constraints (30.8%) and inadequate infrastructure (30.8%) remain major hurdles. Employment data shows a high unemployment rate (38.5%) despite government job reservations (27.7%). Political participation is moderate, with 38.5% perceiving the policies as only slightly effective. Representation in local governance is limited, with 33.8% reporting low levels and 30.8% reporting none. Awareness of reservation policies is varied, with 38.5% being fully aware. However, the effectiveness of these policies is questioned, with only 15.4% considering them highly effective. Skill development programs should be more utilized, with 72.3% not participating. Satisfaction with government support schemes is mixed, with 46.2% expressing satisfaction. The study emphasizes the need for targeted interventions to improve educational quality, enhance employment opportunities, and strengthen political participation and representation. Addressing these challenges is crucial for advancing social justice and ensuring the equitable distribution of resources and opportunities in the Tumkur district.